APPLYING WHATSAPP GROUP TO DEVELOP STUDENTS’ WRITING SKILL FOR JUNIOR HIGH SCHOOL STUDENTS - Refa'i Refa'i; Fitri Palupi Kusumawati; Yunita Kurniati (Journal of English Education and Entrepreneurship (JEEP), 2023)
This reseach is aimed to improve Students Writing Ability through a Whatsapp Group and know how the classroom situation when the students practice their writing ability through the Whatsapp Group. It is a classroom action research undertaken at SMPN 8 Metro in 2020/2021 academic year. The subject of the study was 22 students of the eighth grade. It was completed in two cycles. The criteria of success put in this study, if the students have big interests and high motivation in writing practices through WhatsApp group and get a minimum standard of 60.4 score. The data yielded by conducting classical teaching activity, doing interviews, observations, and tests. The data were analyzed descriptively and simple statistically. The pre-test result showed that the average score gained by the students in the pre-cyclewas less than 60.4(78.12%).Only 5 students (21.88%) got 75 scores, otherwise 17 students (63.64%) were under the passing grade. Then, the students who got score ≥ 75 in post test of cycle 1 were 63.64% or 14 students while 36.36% or 8 students got score < 75. Furthermore, in post test of cycle 2 showed that 85 % of the students got ≥ 75 scores. Furthermore, the classroom situation before the treatment was classified into low category with the mean score of 56.00 or . Then, the students’ activity after the treatment in cycle I increase significantly with the mean score 64. There were 16 active students (72.72%). The average of score yielded in cycle 2 was classified into high category with the mean score of 80 and the number of active students became 19 students (86.36%). Thus, it can be concluded that WhatsApp group is able to improve students’ writing ability. Therefore, it is recommended implemented by teachers in practicing English writing.